Tamasin Day-Lewis: The Art of the Tart - Davidson, Alan E (Petits Propos Culinaires, 2025)
Tamasin Day-Lewis: The Art of the Tart: Cassell and Co., London, 2000: ISBN 0-304-35439-2: 144 pp., colour photos, index, h/b, £16.99.